Aplikasi Mikoriza Arbuskula dan Frekuensi Penyiraman terhadap Pertumbuhan Bibit Tebu (Saccharum oficinarum) Single Bud - Dwi Astutik; . Devi (Politeknik Kelapa Sawit Citra Widya Edukasi, 2020)
Sugar cane plantations are often located on uplands with low irrigation water sources and get water sources from rainfall. Mycorrhiza increased water absorption and effective in dry land. This research aims to determine the best watering frequency and dose of mycorrhizae for sugarcane single bud seedlings. The research was conducted at Research Garden of KUD Ngajum located in Wonosari, Malang, East Java. The research was conducted in May to August 2013. The research method was used a Completely Randomized Design (CRD) consisting of two factors. The first factor was mycorrhizal dose consisting of 4 levels: without mycorrhiza (M0), 10 g /plant (M1), 30 g/plant (M2), 50 g/plant (M3). The second factor was the frequency of watering consists of 4 levels: once a day (F1), once every two days (F2), once every three days (F3), four days (F4). Application of mycorrhizae of 10 grams, 30 grams and 50 grams had the same effect on all parameters of sugarcane seedling growth except the number of tillers, leaf area and percentage of mycorrhizal infection. Frequency of watering every 2 days gives good results on the parameters of plant dry weight. The combination of 50 grams of mycorrhizal treatment with watering frequency once every 2 days gives a good effect on leaf area while the combination of treatment of 10 grams of mycorrhizae and watering once every 4 days and my dose of 30 grams of mycorrhizae with frequency of watering once every 3 days gives a good effect on the percentage of mycorrhizal infections.